Functional cognitive performance augments cognitive screening data in older adults - Marks, Timothy S.; Giles, Gordon Muir; Edwards, Dorothy Farrar (Frontiers in Aging Neuroscience, 2025)
BackgroundUnderstanding the association of older adults’ cognitive ability with performance of instrumental activities of daily living (IADL) is critical to identifying their community health care support needs. We compared differences in performance-based IADL assessment scores among older adults according to their cognitive ability as measured by the Montreal Cognitive Assessment (MoCA).MethodsUsing data from a larger study we performed a cross-sectional analysis of 259 community-dwelling adults aged 55–93 years. Participants were categorized into one of three groups based on their MoCA score: mildly impaired (19–22), borderline (23–25), or unimpaired (26–30). The Performance Assessment of Self-care Skills Checkbook Balancing and Shopping Task (PCST) and the Weekly Calendar Planning Activity 17-item version (WCPA-17) were used to assess IADL. A MANCOVA analyzed the effect of MoCA group on the performance-based IADL assessments while controlling for education.ResultsThe MANCOVA was statistically significant, F(4, 508) = 16.445, p < 0.001; Wilks’ λ = 0.784; ηp2 = 0.115. Follow-up univariate ANCOVAs showed that PCST Total Cues adjusted mean score [F(2, 255) = 20.006, p < 0.001; ηp2 = 0.136] and WCPA-17 Accuracy adjusted mean scores [F(2, 255) = 23.216, p < 0.001; ηp2 = 0.154] were significantly different among MoCA groups, with medium-large effect sizes.ConclusionThe tripartite group categorization of the MoCA largely parallels ability on two independent performance-based IADL assessments, a subset of individuals borderline or unimpaired on the MoCA had difficulties with complex IADL identified by performance-based IADL assessments indicating comprehensive evaluations of older adults would benefit from including both types of assessments.